Representatives of future generations as promoters of sustainability in corporate decision processes - Julia Bogacki; Peter Letmathe (Business Strategy and the Environment, 2021)
Current protests of the young generation emphasize that interests of future generations should be taken more into account by policy makers and in corporate decision processes. As organizations contribute to enduring environmental and social problems, they are required to promote sustainability in order to preserve options for the well-being of future generations. However, organizational decision makers often take a short-term perspective and neglect investments in intergenerational justice. Previous theoretical work has acknowledged the importance of representing future generations in today's decision-making processes to adopt a long-term perspective in order to promote intergenerational justice. In a laboratory experiment, we show that appointing representatives of future generations at the organizational level can foster investments in intergenerational justice. Although this outcome is more pronounced when aligned with the representatives' individual incentives, it even persists for a representative who is monetarily penalized for advocating the interests of future generations.
Keywords: 330; intergenerational justice; negotiation; organizational behavior; representative of future generations; sustainability